Participatory multi-criteria decision analysis to prioritize management areas that help suppress wildfires - Rodríguez-Fernández, Sergio; Murphy, Philip J.; Reynolds, Keith M.; Poudel, Srijana; González-Olabarria, José Ramón; Borges, José G. (Frontiers in Forests and Global Change, 2025)
Effective wildfire prevention and suppression demand spatially targeted fuel management strategies, particularly in fire-prone regions. Despite advances in fire modelling, limited attention has been given to participatory approaches that integrate stakeholder knowledge into spatial prioritization frameworks. This study addresses this gap by developing a spatial decision-support framework that incorporates stakeholder preferences into wildfire prevention planning through a participatory Multi-Criteria Decision Analysis (MCDA) approach. The methodology was applied in Vale do Sousa, a high wildfire-risk region in northern Portugal, where expert knowledge and stakeholder input were combined to prioritize fuel treatment areas. The Ecosystem Management Decision Support (EMDS) system was used to implement the decision model across 2,429 afforested management units. Stakeholder performance in pairwise comparisons was evaluated using three complementary measures: Consistency Ratio (CR), Spearman’s rank correlation coefficient (S), and Euclidean Distance (ED). The results of this performance analysis were integrated into a composite weighting scheme to reflect both the coherence and the level of agreement of individual judgments. These adjusted stakeholder weights were then used to aggregate the AHP-derived criterion and sub-criterion weights, ensuring a balanced representation of diverse perspectives in the final prioritization. The results showed that 1.2% of the study area was classified as ‘very high’ priority and an additional 7.9% as ‘high’ priority, identifying locations where management resources should be concentrated to maximize preventive impact. This approach enhances the transparency, and scalability of participatory planning and supports the spatial prioritization of areas where to allocate resources to enhance wildfire suppression efforts at the landscape scale.